ANTIMICROBIAL POTENTIAL OF ETHANOLIC LEAF EXTRACTS OF PARKINSONIA ACULEATE USING RESPONSE SURFACE METHODOLOGY - YOUNAS, NS; ALI, I; ASHRAF, H; BUKHARI, NT (Biological and Clinical Sciences Research Journal, 2022)
Plant extracts are commonly used to inhibit bacterial activities. In the current analysis, we aimed to study the antimicrobial activity of Parkinsonia aculeata. The plant powder was used to extract the phytocompounds present in the plant by standard method. Then this extract was used to inhibit the growth of different bacteria at different pH, temperate and concentration. Antimicrobial activity was noted under different conditions. These results showed that Parkinsonia aculeata has very important antibacterial compounds such as phenols, flavonoids, tannins, and alkaloids depicting promising antibacterial activity for various bacterial ailments but at a specific temperature, pH and concentration. Escherichia coli showed growth restriction at the optimal pH 5.0, temperature 35°C and concentration 5-10mg/dl. Salmonella typhi growth was inhibited at the optimal pH 5.0, temperature 35°C and concentration 9.4-10 mg/dl. Similarly, the Klebsiella pneumoniae offered the inhibition rate at the optimal pH 5-7, temperature 35.2°C and concentration 5.0-7.0mg/dl. All of these results were confirmed by contour plots by Response Surface Methodology. Hence, it is suggested from this research work that Parkinsonia aculeata, when used at proper pH, temperature and concentration, can be employed to treat various bacterial inflammations in the biological system.